China's footprint in global financial markets - David Lodge; Ana-Simona Manu; Ine Van Robays (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
Using daily data since 2017, we disentangle China-specific structural shocks driving Chinese financial markets and examine spillovers across global markets. The novelty of this paper consists of simultaneously identifying China shocks with shocks emanating from the United States and shocks to global risk sentiment - two major forces driving global financial markets - to ensure that China spillover estimates do not reflect common factors. Our results show that shocks originating in China have material impacts on global equity markets, although spillovers are much smaller than those following shocks in the United States, or those triggered by shifts in global risk sentiment. By contrast, shocks from China account for a significant proportion of variation in global commodity prices, more on a par with those of the United States. Nevertheless, spillovers from China can be significantly amplified in an environment of heightened global volatility, or when the shocks are large.
urn:nbn:fi-fe202402157429
Keywords: E44; E52; G15; 330; China shocks; spillovers; global financial markets; commodities